2014
DOI: 10.1097/hjh.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renal nerve morphological changes and norepinephrine levels following treatment with novel bipolar radiofrequency delivery systems in a porcine model

Abstract: Objective:To evaluate the safety and effectiveness of different bipolar radiofrequency system algorithms in interrupting the renal sympathetic nerves and reducing renal norepinephrine in a healthy porcine model.Methods:A porcine model (N = 46) was used to investigate renal norepinephrine levels and changes to renal artery tissues and nerves following percutaneous renal denervation with radiofrequency bipolar electrodes mounted on a balloon catheter. Parameters of the radiofrequency system (i.e. electrode lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…These findings corroborate recent studies showing significant reductions in renal norepinephrine 8 weeks after RDN in obese hypertensive dogs 19 and 1 and 4 weeks after RDN in normal pigs. 18 In addition, after RDN we found inhibition of the afferent response to electric stimulation and decreased levels of CGRP staining.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These findings corroborate recent studies showing significant reductions in renal norepinephrine 8 weeks after RDN in obese hypertensive dogs 19 and 1 and 4 weeks after RDN in normal pigs. 18 In addition, after RDN we found inhibition of the afferent response to electric stimulation and decreased levels of CGRP staining.…”
Section: Discussionmentioning
confidence: 89%
“…These findings corroborate recent studies showing significant reductions in renal norepinephrine 8 weeks after RDN in obese hypertensive dogs 19 and 1 and 4 weeks after RDN in normal pigs. 18 In addition, after RDN we found inhibition of the afferent response to electric stimulation and decreased levels of CGRP staining.Interestingly, we found that by 5.5 months after RDN there was almost complete functional and anatomic reinnervation, and by 11 months after denervation there were no differences in the responses to electric stimulation, renal distribution of TH and CGRP, or renal norepinephrine levels compared with nondenervated controls. Importantly, by demonstrating unambiguously different responses to stimulation of the proximal and distal ends of the cut renal nerve we were able to demonstrate normalization of both the afferent and efferent responses to stimulation of the intact renal nerves.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…14,17,18 Effective RF nerve ablation has been previously shown to decrease NE levels in large animal models. 19,20 In this study, the norepinephrine levels measured in the single ablation animals demonstrated a significant NE decrease at all time points compared to naïve kidneys. The dramatic drop at 7 and 30 days, interestingly, is attenuated at 90 days, albeit still statistically decreased compared to controls.…”
Section: Discussionmentioning
confidence: 94%
“…14,[24][25][26] The high degree of distal nerve atrophy observed at 7 and 30 days in this study reported at chronic time points in other large animal experiments where RF ablation of renal nerves was performed. 14,20 It is necessary to further establish if the apparent morphological "recovery" of distal nerves could be responsible for the late increase in NE levels and whether this partial recovery may or may not produce a physiologic increase in blood pressure. The available clinical data though suggest sustained blood pressure lowering effects up to 36 months following the procedure.…”
Section: Discussionmentioning
confidence: 99%